Pengaruh Model Pembelajaran Problem Based Learning Berbantuan Media PSA (Panggung Siklus Air) Terhadap Kemampuan Berpikir Kritis Siswa - Sari, Intan Nila; Ardianti, Sekar Dwi; Khamdun, Khamdun (Institut Agama Islam Daruttaqwa Gresik, 2023)
This study aims to determine the effect of using the problem-based learning model assisted by the water cycle stage media on students' critical thinking skills. The use of learning models can affect students' critical thinking skills. In this study using the Problem Based Learning learning model. The population in this study were fifth-grade students at SD N Ngawen 02, with a total of 22 students. This research is a quantitative study, taking samples using a random sampling technique, each population has the same opportunity to be randomly selected. one experimental class. This study used a paired sample t-test with a significant value of 2-tailed, namely obtaining 0.000 <0.05 so that H_o was rejected and H_a was accepted. Before being given treatment, the initial average value was 50.1. After being given treatment, the average was 88.6 using the problem-based learning model assisted by the water cycle stage media. It can be concluded that using the problem-based learning model is significantly better at improving students' critical thinking skills.